Pemenuhan Hak Rekreasional terhadap Anak Binaan di Lembaga Pembinaan Khusus Anak (LPKA) Kelas I Blitar - Jessy Yolandita Dewi (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Recreational is one of the rights of the Built Child while they are serving at the Special Development Institution for Children (LPKA). However, there are still children in LPKA who don’t understand that they have recreational rights attached to them. The purpose of this study was to find out about the fulfillment of the recreational rights as well as the obstacles encountered in fulfilling the recreational rights in Class I Special Development Institutions for Children (LPKA). This research method is empirical juridical. Primary data and secondary data are used by obtaining through interviews, questionnaires, and literature studies. The analytical method used is analytical descriptive. The results of the research are that the fulfillment of recreational rights in LPKA Class I Blitar has been fulfilled but has not been maximized in its implementation because there are constraints both from internal factors and from external factors such as limited budget and facilities & infrastructure, limited experts, enthusiasm of the built children themselves, security , the existence of the covid-19 pandemic, negative stigma from society, and also related to the marketing of the results of the skills of the Built Children. However, with these constraints, various efforts can be made to overcome them.